Lightning rod on the church: Heritage as faith in a meaningful past - Popadić, Milan M. (Collection of Papers of the Faculty of Philosophy in Priština, 2015)
In the paper Fabricating Heritage David Lowenthal distinguishes between history and heritage, and says that history seeks to convince by truth, and succumbs to falsehood, while heritage exaggerates and omits, candidly invents and frankly forgets, and thrives on ignorance and error. As Lowenthal states, heritage uses historical traces and tells historical tales, but these tales and traces are stitched into fables closed to critical scrutiny, because it is not erudition but catechism – not checkable fact but credulous allegiance. Hence the Lowenthal’s conclusion: Heritage is not a testable or even plausible version of our past; it is a declaration of faith in that past.  Starting from these positions, this paper will examine the relationship between the scientific approach to the problem of heritage and heritage processes independent of institutionalized protection system (“heritage catechism”). What we want to preserve is a specific quality, the quality of testimonial nature. It is the quality of the aforesaid forms and contents that have overcome past in order to testify, hence to fully inform us of the reality from which they originated and while testifying about that reality, they synchronously testify about those who care about them nowadays. Although seemingly paradoxical, like a lightning rod in the church, this paper defends the thesis that for the lasting care for heritage, and thus for a comprehensive understanding of the meaning of the past, synergy of scientific and “catechistic” approach to heritage is necessary.
Keywords: meaningful past; „heritage catechism”; heritology; heritage